Describing the hexapeptide identity platform between the influenza A H5N1 and Homo sapiens proteomes - Darja Kanduc (Dove Medical Press, 2010)
Darja KanducDepartment of Biochemistry and Molecular Biology, University of Bari, ItalyAbstract: We searched the primary sequence of influenza A H5N1 polyprotein for hexamer amino acid sequences shared with human proteins using the Protein International Resource database and the exact peptide matching analysis program. We find that the viral polyprotein shares numerous hexapeptides with the human proteome. The human proteins involved in the viral overlap are represented by antigens associated with basic cell functions such as proliferation, development, and differentiation. Of special importance, many human proteins that share peptide sequences with influenza A polyprotein are antigens such as reelin, neurexin I-a, myosin-IXa, Bardet–Biedl syndrome 10 protein, Williams syndrome transcription factor, disrupted in schizophrenia 1 protein, amyotrophic lateral sclerosis 2 chromosomal region candidate gene 17 protein, fragile X mental retardation 2 protein, and jouberin. That is, the viral-vs-human overlap involves human proteins that, when altered, have been reported to be potentially associated with multiple neurological disorders that can include autism, epilepsy, obesity, dystonia, ataxia–telangiectasia, amyotrophic lateral sclerosis, sensorineural deafness, sudden infant death syndrome, Charcot-Marie-Tooth disease, and myelination. The present data are discussed as a possible molecular basis for understanding influenza A viral escape from immunosurveillance and for defining anti-influenza immune-therapeutic approaches devoid of collateral adverse events.Keywords: peptide sharing, neurological disorders, host-pathogen relationships, viral escape from immunosurveillance